2013
DOI: 10.1086/672358
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Game: Assessing the Impact of Cultural Representations on Consumer Perceptions of Legitimacy

Abstract: The purpose of this article is to understand how media frames affect consumer judgments of legitimacy. Because frames exist on the sociocultural and individual level, our research takes a multimethod approach to this question. On the sociocultural level, we conduct a content analysis of operant media frames for discussing online gambling and perform an event analysis, finding that a shift in consumer judgments follows an abrupt shift in frame. Then, on the individual level, the causal mechanism for these shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 65 publications
(93 reference statements)
4
133
0
7
Order By: Relevance
“…The use of marketing to spread acceptance for social messages requires pre-existing cultural knowledge to be in place [87]. This includes broader cultural trends as well as context specific to the social message.…”
Section: Creating Receptive Audiencesmentioning
confidence: 99%
“…The use of marketing to spread acceptance for social messages requires pre-existing cultural knowledge to be in place [87]. This includes broader cultural trends as well as context specific to the social message.…”
Section: Creating Receptive Audiencesmentioning
confidence: 99%
“…Prior research on legitimacy and media frames has shown that media evaluations affect normative legitimacy (Deephouse 1996;Zimmerman and Zeitz 2002). However, Humphreys and LaTour (2013) maintain that media frames do not just result in changes to normative evaluations, but can directly impact cognitive evaluations as well. Their research revealed that when the new label ''gaming'' replaced the old label ''gambling,'' nongamblers responded positively and ''had more associations with the legitimate practice after being shown the new label, ''gaming'' (Humphreys and LaTour 2013, p. 788).…”
Section: Media Framing and Legitimacymentioning
confidence: 92%
“…Thus, although the newspapers may cater to a different readership and present a different focus-'center, right business' versus 'liberal news story and editorial'-they were chosen for this study due to their agenda-setting capacity. Moreover, as previously indicated, media accounts reflect the development of cognitive legitimacy (Baum and Powell 1995;Dowling and Pfeffer 1975;Hannan et al 1995;Humphreys and LaTour 2013) and are therefore useful in studies of organizational legitimacy (Deephouse and Suchman 2008). A keyword search in the LexisNexis archive was conducted for the search terms ''nongovernmental organi*ation''-the asterisk representing either an ''s'' or ''z''-from 1985 to 2010.…”
Section: Methods Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations